2020
DOI: 10.3390/jmse8030181
|View full text |Cite
|
Sign up to set email alerts
|

Combined Depth Control Strategy for Low-Speed and Long-Range Autonomous Underwater Vehicles

Abstract: Autonomous underwater vehicles (AUVs) are increasingly being applied to highly detailed survey and inspection tasks over large ocean regions. These vehicles are required to have underwater hovering and low-speed cruising capabilities, and energy-saving property to enable long-range missions. To this end, a combined depth control strategy is proposed in which an on-off type variable ballast system (VBS) is adopted for satisfactory hovering or fast descending/ascending without propulsion to reach the designated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…While the study indicates some advantages of hybrid strategies, uncertainties remain regarding the generalizability of results to different depth steps and the absence of experiments including VBM deactivation or buoyancy disturbances. Bi et al [18] proposed a hybrid depth control strategy integrating an on-off hydraulic VBM for swift depth adjustments and fin control for energy conservation during cruising with propellers. The strategy enables efficient diving and surfacing without propeller usage and effective hovering control with low power consumption.…”
Section: Introductionmentioning
confidence: 99%
“…While the study indicates some advantages of hybrid strategies, uncertainties remain regarding the generalizability of results to different depth steps and the absence of experiments including VBM deactivation or buoyancy disturbances. Bi et al [18] proposed a hybrid depth control strategy integrating an on-off hydraulic VBM for swift depth adjustments and fin control for energy conservation during cruising with propellers. The strategy enables efficient diving and surfacing without propeller usage and effective hovering control with low power consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the great challenges associated with the problem of AUV control subject to uncertainties, the research community has increased its efforts to find new strategies to achieve solutions for different control objectives related to underwater robots such depth control, station-keeping, trajectory tracking, path-following, fault tolerant control, or docking operations [15][16][17][18]. Research studies have demonstrated that intelligent control techniques ( [19,20]) are highly effective to deal with this type of problem because of their adaptive and robustness nature.…”
Section: Introductionmentioning
confidence: 99%